Chemical composition and carbohydrates of seaweed Sargassum sp. with different drying methods - Paga, Agustinus ; Suek, Ferdinand Suharjo (Fakultas Peternakan Universitas Papua, 2024)
Sargassum sp., a brown seaweed abundant in Semau Island, East Nusa Tenggara, Indonesia, has potential as an alternative feed source in animal nutrition due to its rich chemical composition. This study aimed to determine Sargassum sp.'s chemical and carbohydrate composition using different drying methods to evaluate its suitability as livestock feed. A Completely Randomized Design (CRD) with three treatments—sun drying, oven drying at 60°C, and air drying—and five replications were employed. Using standard proximate analysis, fresh seaweed samples were dried according to the treatments and analyzed for dry matter, organic matter, crude protein, crude fat, crude fiber, and carbohydrate content. The results showed that the drying method significantly affected (P < 0.05) the dry matter, moisture content, ash content, organic matter, crude protein, and crude fat of Sargassum sp. but had no significant effect (P > 0.05) on crude fiber and carbohydrate content. Air-dried samples exhibited the highest crude protein content (6.38%) compared to sun-dried (4.71%) and oven-dried (4.94%) samples, indicating better preservation of protein at lower temperatures. Crude fat content was highest in sun-dried samples (0.56%) and lowest in air-dried samples (0.24%). Carbohydrate content ranged from 52.83% to 54.00% across all treatments without significant differences. These findings suggest that air drying is the most effective method for retaining the nutritional components of Sargassum sp., enhancing its potential as a valuable ingredient in animal feed formulations. The drying method significantly influences Sargassum sp. seaweed's chemical composition. Air drying preserves key nutritional components, making it the recommended method for processing Sargassum sp. for use in animal nutrition.